1993
DOI: 10.1016/0014-5793(93)81774-t
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes induces selective alterations in the expression of protein kinase C isoforms in hepatocytes

Abstract: Membrane and cytosol fractions from hepatocytes of both normal and streptozotocin-induced diabetic animals were probed with a panel of polyclonal anti-peptide antisera in order to identify protein kinase C (PKC) isoforms. Immunoreactive species were noted with antisera specific for ~ (-81 kDa), fl-ll (-82 kDA), E (--95 kDa) and ~" (~ 79 kDa). In addition, a species migrating with an apparent size of -94 kDa was also detected in cytosol fractions using an antiserum specific for PKC-c~. Each of these species was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 55 publications
3
37
1
Order By: Relevance
“…Additional supportive evidence is the amelioration of the glucose uptake in cells treated with both oleate and the Bis-I, but not in cells treated with palmitate. PKC activation has been implicated in several studies of insulin resistance and diabetes and even in the absence of lipid oversupply [11,25,26]. The inhibitory effects of PKC on insulin signaling may at least in part be explained by the more recently identified role of the serine/ threonine phosphorylation of IRS-1, which has been implicated in the inhibition of its tyrosine phosphorylation [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Additional supportive evidence is the amelioration of the glucose uptake in cells treated with both oleate and the Bis-I, but not in cells treated with palmitate. PKC activation has been implicated in several studies of insulin resistance and diabetes and even in the absence of lipid oversupply [11,25,26]. The inhibitory effects of PKC on insulin signaling may at least in part be explained by the more recently identified role of the serine/ threonine phosphorylation of IRS-1, which has been implicated in the inhibition of its tyrosine phosphorylation [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The abundant hepatic proteins identified in our analysis included PDI, ER60, peroxiredoxin 4, aldolase B, glutathione S-transferase, retinol-binding protein, cytochrome b 5 , nonmuscle actin, 40 S ribosomal protein SA, ATPase, BiP, and calreticulin (49 -62). RACK1, which was shown not to be expressed differentially in the hepatic ER, is associated with the hepatic ER through its interaction with protein kinase C-␤ (63)(64)(65)(66)(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%
“…In an early study on hepatocytes of both normal and streptozotocin-induced diabetic animals [142], it was reported that streptozotocin increased levels of the PKCβII and α, with no change in the level of PKCς. Diabetes induction also appeared to have elicited the translocation of PKCβII and PKCα to the membrane fraction.…”
Section: Additional Studies On Animal Modelsmentioning
confidence: 99%